Determination of employee turnover intention through job satisfaction: work family conflict and organizational commitment - Selvi Yona Sari; Havidz Aima; Zefriyenni Zefriyenni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Human resources are something that needs to be considered in facing the development of the banking industry. This research aims to test and prove empirically the direct and indirect influence of Work Family Conflict and Organizational Commitment on Turnover Intention with Job Satisfaction as an intervening variable. This study uses a quantitative approach. The population consists of permanent employees from PT Bank Nagari in West Sumatra Tbk. With a total sample of 319 employees. The method used is Partial Least Square (PLS) analysis with the SmartPLS application. The results of the research show that there are eight direct influences from this research, namely that work family conflict has no effect on job satisfaction and employee retention, there is an effect of organizational commitment on job satisfaction, work family conflict has an effect on turnover intention, organizational commitment, job satisfaction and employee retention has no effect. on turnover intention. Meanwhile, the four indirect influences are job satisfaction.